1999
DOI: 10.1063/1.480146
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of ammonia on the rhodium (111), (100), and stepped (100) surfaces: An ab initio and experimental study

Abstract: The adsorption of ammonia on the two low index ͑111͒ and ͑100͒ surfaces of rhodium has been studied by periodic calculations with density functional theory and compared to experimental results. The geometries of the adsorbates and the surfaces are completely optimized. For both surfaces the top site is found to be the most stable while the adsorption energy of ammonia is 8-10 kJ•mol Ϫ1 larger on the ͑100͒ surface. The presence of steps on the ͑100͒ surface has a minor effect on the heat of adsorption. The theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…It was moreover concluded that the adsorption site on top of Rh atoms at the bottom of the step is unstable; NH 3 molecules present there experience a significant repulsion from the step itself and migrate to the top sites in the middle of the terrace (E ads = 93 kJ/mol) or to the tilted site at the step (E ads = 98 kJ/mol). Such E ads values compare well with those of 82 kJ/mol and 91 kJ/mol predicted theoretically for Rh (111) and Rh(100), respectively, and with the experimental values estimated from the analysis of TPD spectra [382].…”
Section: N H 3 Adsorption At Flat and Stepped Rh Surfacessupporting
confidence: 70%
See 2 more Smart Citations
“…It was moreover concluded that the adsorption site on top of Rh atoms at the bottom of the step is unstable; NH 3 molecules present there experience a significant repulsion from the step itself and migrate to the top sites in the middle of the terrace (E ads = 93 kJ/mol) or to the tilted site at the step (E ads = 98 kJ/mol). Such E ads values compare well with those of 82 kJ/mol and 91 kJ/mol predicted theoretically for Rh (111) and Rh(100), respectively, and with the experimental values estimated from the analysis of TPD spectra [382].…”
Section: N H 3 Adsorption At Flat and Stepped Rh Surfacessupporting
confidence: 70%
“…With increasing coverage low-temperature shoulders extending down to 150 K appear in the TPD spectra of both surfaces. There is no general agreement on the interpretation of these features; they are explained either as due to a decrease in the heat of adsorption caused by lateral interactions [383] or as an entropy effect affecting the pre-exponential factor at increasing coverage [382]. It seems, however, established that the presence of steps on the (100) surface marginally affects the heat of adsorption, in agreement with the fact that the bond strength changes only by 10% between Rh(111) and Rh (100).…”
Section: N H 3 Adsorption At Flat and Stepped Rh Surfacesmentioning
confidence: 94%
See 1 more Smart Citation
“…This is due to the interaction between the nonbonding lone pair of NH 3 and the substrate involved in the NH 3 -substrate bond [8] . We further found that rotation of the molecule results in only small difference in the adsorption energy, which implies that the barrier of rotation is negligible, similar to the ammonia adsorption on Pt{100} [9] , Pt{111} [9] , Rh{100} [8] , and Rh{111} [8] .…”
Section: Physical Chemistrymentioning
confidence: 99%
“…Rh{100} [8] . This is due to the interaction between the nonbonding lone pair of NH 3 and the substrate involved in the NH 3 -substrate bond [8] .…”
Section: Physical Chemistrymentioning
confidence: 99%